Improving SEL outcomes for US 9th graders: Results from a District Wide School Reform. (December 2022) - Rosen, Jeffrey A.; Hong, Yihua; Rutledge, Stacey; Cannata, Marisa; Rotermund, Susan; Leu, Katherine
Abstract: This study examined the impact of Personalization for Academic and Social Emotional Learning (PASL), a school-based social emotional reform implemented in the Broward County Florida Public Schools. Taking advantage of a phased roll out of PASL, we analyzed data collected during the first implementation year (2017–18) and compared 205 9th grade students in 6 schools that received PASL with 1139 comparison group students in 5 schools that received PASL in later years. Focusing on student social emotional outcomes, including school engagement, self-efficacy, and self-regulation, we found that PASL effects, though small and insignificant on average, might vary by students and depend on their initial engagement at the beginning of the 9th grade. The lower a student's initial engagement, the stronger the PASL effects on end-of-year engagement and self-efficacy. Highlights: PASL could increase student engagement meaningfully in the SEL context. The lower a student's engagement pre 9th grade, the stronger the PASL impact. PASL does not produce main effects on self-efficacy and self-regulation.